MASJID SUMPAH : WISATA RELIGI KELURAHAN MASIGIT KOTA CILEGON - Jakaria, Jakaria (Jurnal Pengabdian Dinamika, 2021)
Of the many potential tourist objects owned by the City of Cilegon, the most interesting for the author to be used as an object of research is the religious tourism object of the Oath Mosque which is located in the Terate Udik neighborhood, RT 02/02. This mosque is an ancient mosque that is historical in the development of Islam because it existed before the kingdom of Banten. The building structure is in the form of a 5 (five)-story mamolo which has a philosophical meaning of an invitation to carry out the5 (five) pillars of Islam, and can also be interpreted as an invitation to perform the obligatory prayers 5 (five) times a day. The methodology used in this research is descriptive qualitative, namely as a procedure that produces descriptive data in the form of written or spoken words from people. Masigit Village has more than one tourist attraction that is not widely known by the public. The Oath Mosque and the Tomb of Rouf Jaya Laksana Village Head are real examples of tourism objects in the religious field in Masigit Village, Cilegon City, Banten.